2016
DOI: 10.1371/journal.pone.0150950
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Historical Sea Level Rise and Contemporary Ocean Currents on Regional Gene Flow of Rhizophora racemosa in Eastern Atlantic Mangroves

Abstract: Mangroves are seafaring taxa through their hydrochorous propagules that have the potential to disperse over long distances. Therefore, investigating their patterns of gene flow provides insights on the processes involved in the spatial genetic structuring of populations. The coastline of Cameroon has a particular geomorphological history and coastal hydrology with complex contemporary patterns of ocean currents, which we hypothesize to have effects on the spatial configuration and composition of present-day ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 110 publications
(135 reference statements)
6
45
0
Order By: Relevance
“…, Ngeve et al . ). Our results confirm that oceanic processes such as eddies could alter the dispersal trajectories of drifting organisms (Sponaugle et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Ngeve et al . ). Our results confirm that oceanic processes such as eddies could alter the dispersal trajectories of drifting organisms (Sponaugle et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Ngeve et al . ). However, these models typically do not include interactions between wind and water currents as drivers for the transport of propagules with different traits.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the latter, the divergence was attributed to the fruiting season that coincided with northward-flowing ocean currents cutting through the South China Sea into the Pacific Ocean, thus preventing dispersal between populations from the east and west corners of the South China Sea [49]. Landscape level propagule release simulations, which account for ocean circulation patterns, will be able to cross-validate these inferences [50].…”
Section: Strong Influence Of Vicariance and Oceanic Barriers On Genetmentioning
confidence: 99%
“…To date, only a few species in estuary have been studied on their genetic structure and researchers mainly focused on a small group of animals (Bible & Sanford, ; Bilton, Paula, & Bishop, ; Dennenmoser, Vamosi, Nolte, & Rogers, ; McCairns & Bernatchez, ; Sanford & Kelly, ) while few higher plant species have been studied (Bilton et al, ; but see, e.g., Ngeve, Stocken, Menemenlis, Koedam, & Triest, ; Ngeve, Stocken, Menemenlis, Koedam, & Triest, ). Additionally, these studies have shown that many are more structured than could be expected despite a lack of barriers of dispersal in estuarine system, suggesting some dispersal limitation through geographical distance, environmental variation, or other cryptic barriers promotes isolation (KesĂ€niemi, Hansen, Banta, & Knott, ).…”
Section: Introductionmentioning
confidence: 99%